Hollywood or history? : an inquiry-based strategy for using film to acknowledge trauma in social studies - Yoder, Paul Jordan; Johnson, Aaron (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Traumagenic events-episodes that have caused or are likely to cause trauma-color the experiences of K-12 students and the social studies curriculum they encounter in U.S. schools. At the same time that the global COVID-19 pandemic has heightened educators' awareness of collective trauma, the racial reckoning of 2020 has drawn important attention to historical and transgenerational trauma. At a time when social studies educators can simply no longer ignore "difficult" knowledge, instruction that acknowledges trauma in social studies classrooms is essential. Through employing relational pedagogies and foregrounding voices that are too often silenced, the lessons in Hollywood or History? An Inquiry-Based Strategy for Using Film to Acknowledge Trauma in Social Studies engage students in examining the role of traumatic or traumagenic events in social studies curriculum. The 20 Hollywood or History? lessons are organized by themes such as political trauma and war and genocide. Each lesson presents film clips, instructional strategies, and primary and secondary sources targeted to the identified K-12 grade levels. As a collection, they provide ready-to-teach resources that are perfect for teachers who are committed to acknowledging trauma in their social studies instruction"-- Provided by publisher.
Keywords: Inquiry-based learning.; Motion pictures in education.; Psychic trauma in children.; Social sciences -- Study and teaching.; History -- Study & Teaching.; Society and culture: general.; General and world history.; Educational: Humanities and social sciences, general.; elektronické knihy; electronic books